Evaluasi Pengaruh Geometri Hauling Road Batubara Terhadap Produksi Dump Truck Iveco 380 Trakker Dari Pit Sari Menuju Stockpile PT. Adimitra Baratama Nusantara, Sangasanga, Kutai Kartanegara, Kalimantan Timur - Fauzi Fitri Nasrul; Ansosry Ansosry (Journals Mining Engineering : Bina Tambang, 2019)
Abstract. Pit Sari coal production target PT. Adimitra Baratama Nusantara in April 2018 amounted to 200,850.0 tons / month, but the amount of coal mined in pit sari in April was only 194.645,27 tons. The combination of transport and loading equipment used is 1 unit Caterpillar 349D excavator with 6 units of Dump Truck Iveco 380 Trakker. After measuring the width of the straight road and the bend, it was found that the condition of the width of the road was not yet in accordance with the wide standard that can be passed by the conveyance. One solution to increase production is to improve road geometry conditions such as increasing the width of the road, decreasing the slope of the road, to pay attention to cross slope and superelevation. Based on the calculation of road geometry evaluation, the width of the straight road and the bend that is passed by OHT Caterpillar 777D is 21,58 meters and 24,08 meters. While for the standard road width passed by Iveco Dump Truck itself is 13,53 meters and 16,08 meters. Road grade > 9% must be reduced to 9%. The cross slope number that must be made is 43,16 cm for the road that is passed by OHT, 27,06 cm for the road that is passed by the Dump Truck Iveco 380 Trakker. The super elevation that must be made is 74 cm. Production after repairs to the haul road geometry reached 217.167,57 tonsKeywords: Dump Truck, Iveco 380 Trakker, Road Geometry, Production, Cycle Time.